Effect of Urbanization on Groundwater Resources Hydrodynamics and Bearing Capacity: a Case Study From the Bayraklı Region, Izmir, ̇ Türkiye - İşbuğa, Volkan; Öztürk,B.; Baba, Alper; İşbuğa,V.; Bilgiç,E.; Baba,A. (Geological Society of London, 2024)
The bearing capacity of soil is a critical factor in the design of foundations for civil engineering structures. The bearing capacity depends on soil properties, as well as the location of the water table. A rise in the groundwater level can be dramatic, especially in highly urbanized regions, and can affect the bearing capacity of foundations. In this study, groundwaterlevel fluctuations in a highly urbanized region in Izmir, the third largest city in Türkiye, was monitored over a 1 year period, and ̇ its effect on reducing the bearing capacity, which is not considered in foundation design and construction, was investigated. For this purpose, four observation wells equipped with groundwater data loggers were used to determine the variations in groundwater level over 1 year. Using the Terzaghi approach to calculate the bearing capacity, normalized bearing capacity plots for various foundation width/depth (B/Df) ratios were generated for all four observation wells. Remarkable bearing capacity changes of 10.94, 8.21, 7.62 and 9.29% were observed in four different observation wells (OW-1, OW-3, OW-6 and OW-9, respectively). The study showed that changes in groundwater level in the region caused by urbanization poses a potential risk to the sustainability of previously constructed foundations. © 2024 The Author(s).
Keywords: [No Keyword Available]